2020
DOI: 10.1186/s12873-020-00387-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic patterns of emergency ambulance assignments for older adults compared with adults requiring emergency care at home in Sweden: a total population study

Abstract: Background Since the vast majority of older adults in Sweden live in their private homes throughout life, the emergency medical services need to adapt accordingly. Hence, we aimed to describe characteristic patterns of dyadic staffed emergency ambulance assignments for older adults aged > 70 years compared with adults aged 18–69 years requiring emergency care at home in Sweden. Methods A descriptive retrospective study was performed using anonym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 42 publications
2
19
0
2
Order By: Relevance
“…The logistic model for both crude data and after adjustment showed that EMS missions for elderly patients were significantly less likely to be associated with the odds of NC due to PIR. This significant association between elderly patients and the low rate of NC due to PIR is consistent with several studies showing the high association between elderly and the transportation by ambulances to EDs [36][37][38][39][40]. Oosterwold J et al, in their systematic review, found that the severity of the medical condition for elderly patients was not the main predictor of conveyance, but there were different factors related to EMS structure and related to the patients themselves [41].…”
Section: Discussionsupporting
confidence: 82%
“…The logistic model for both crude data and after adjustment showed that EMS missions for elderly patients were significantly less likely to be associated with the odds of NC due to PIR. This significant association between elderly patients and the low rate of NC due to PIR is consistent with several studies showing the high association between elderly and the transportation by ambulances to EDs [36][37][38][39][40]. Oosterwold J et al, in their systematic review, found that the severity of the medical condition for elderly patients was not the main predictor of conveyance, but there were different factors related to EMS structure and related to the patients themselves [41].…”
Section: Discussionsupporting
confidence: 82%
“…A significant contributor to this increase is the growing population of older people with greater healthcare needs. This is confirmed by a recent study indicating a considerable increase in dispatched ambulance resources for patients between 70 and 89 years of age, showing that 60% of the assignments involved older patients >70 years of age (Hjalmarsson et al, 2020). Because autonomy is an important ethical value for most patients, it is also important to understand how ambulance clinicians (ACs) perceive and manage patient autonomy.…”
Section: Introductionmentioning
confidence: 75%
“…There is an ongoing global discussion to meet the need of an ageing population by increasing collaboration between healthcare organizations in out-of-hospital settings (NHS, 2019 ; SOU 2020 :19, 2020), such as between ambulance service and primary healthcare (PHC) centres (NHS, 2019 ). The need for ambulance care increases with age (Jones et al, 2017 ), and around 40–60% of patients engaging ambulance services are 65 years or older (Duong et al, 2018 ; Hjalmarsson et al, 2020 ). There is an upward trend for older patients to receive their entire care in out-of-hospital settings, such as in their own home or at PHC centres after calling for an ambulance (Forsgärde et al, 2020 ; Hjalmarsson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The need for ambulance care increases with age (Jones et al, 2017 ), and around 40–60% of patients engaging ambulance services are 65 years or older (Duong et al, 2018 ; Hjalmarsson et al, 2020 ). There is an upward trend for older patients to receive their entire care in out-of-hospital settings, such as in their own home or at PHC centres after calling for an ambulance (Forsgärde et al, 2020 ; Hjalmarsson et al, 2020 ). Not being transported by an ambulance to the emergency department (ED) is also known as non-conveyance to hospitals.…”
Section: Introductionmentioning
confidence: 99%